Impact of Dental Restoration and Extraction Treatments on Oral Health–Related Quality of Life (OHRQoL) - Sulistyawati, Tri; Novika, Revi Gama Hatta; Murti, Bhisma; Cahyanto, Erindra Budi; Demartoto, Argyo (Indonesian Journal of Medicine, 2025)
Background: Cavities or dental caries is one of the most common diseases as the main cause of pain in the oral cavity which can have a significant impact on quality of life. Cavities have several treatment modalities available such as restoration and tooth extraction. These treatment options not only affect the patient's clinical condition, but can also affect the psychological, social, and functional aspects reflected in the Oral Health Related Quality of Life (OHRQoL). The study aimed to determine the effect of restoration treatment and tooth extraction on Oral Health Related Quality of Life (OHRQoL). Subjects and Method: This research was conducted in December 2024 with a total of 200 samples in Surakarta, This study uses a quantitative design with a cross-sectional approach. Data were collected from patients who had undergone restoration treatment and/or tooth extraction on cavities. Dependent variables are in the form of Oral Health Related Quality of Life (OHRQoL) and independent variables in the form of restorative treatments, tooth extraction, age and gender. Data were analyzed by double linear regression. Results: Multiple linear regression analysis showed a significant negative association between the type of dental treatment and OHRQoL. Patients who underwent tooth extraction had OHRQoL scores that were 26.89 units lower than those who received restorative treatment (b = -26.89; 95% CI = -29.39 to -24.39; p < 0.001). No significant association was found between age or sex and OHRQoL. Conclusion: Dental restoration treatments have a significant influence on improving Oral Health Related Quality of Life (OHRQoL), while tooth extraction shows a positive but insignificant relationship. Age and sex variables had no statistical effect on OHRQoL.